2004
DOI: 10.1088/0965-0393/12/2/008
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation sequence in niobium-alloyed ferritic stainless steel

Abstract: Niobium is an important alloying element in the design of heat-resistant ferritic stainless steels for automotive exhaust systems. When in solid solution, it improves both the high temperature strength and the resistance to thermal fatigue. However, it also forms several kinds of precipitates during service. These reactions have been modelled, taking into account the multicomponent nature of the diffusion process and allowing for capillarity effects. It has been possible to estimate not only the volume fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 26 publications
2
30
0
2
Order By: Relevance
“…The most general method used to obtain the interface energies is estimation of interface energy from experimental data of precipitate coarsening rate with help of Ostwald ripening law. [1][2][3][4][5][6] Recently, a discrete lattice plane/nearest neighbor broken bond (DLP/NNBB) approach was also employed by Yang and Enomoto 7) to calculate the energy of interfaces formed between ferrite (bcc Fe) and carbides or nitrides of Ti, V, Zr and Nb. The required bond energies in this approach were evaluated from the semi-empirical model of de Boer et al 8) Because of lack of reliability in estimation of interface energy by empirical and semi-empirical methods, ab initio (first principles) method with high physical accuracy has been recently used to calculate the metal/carbide and metal/nitride interface energies.…”
Section: Introductionmentioning
confidence: 99%
“…The most general method used to obtain the interface energies is estimation of interface energy from experimental data of precipitate coarsening rate with help of Ostwald ripening law. [1][2][3][4][5][6] Recently, a discrete lattice plane/nearest neighbor broken bond (DLP/NNBB) approach was also employed by Yang and Enomoto 7) to calculate the energy of interfaces formed between ferrite (bcc Fe) and carbides or nitrides of Ti, V, Zr and Nb. The required bond energies in this approach were evaluated from the semi-empirical model of de Boer et al 8) Because of lack of reliability in estimation of interface energy by empirical and semi-empirical methods, ab initio (first principles) method with high physical accuracy has been recently used to calculate the metal/carbide and metal/nitride interface energies.…”
Section: Introductionmentioning
confidence: 99%
“…It could be concluded that an interfacial energy value between 0.1 and 0.2 J/m 2 reproduced the measured coarsening rate. This interfacial energy value is a bit lower than, but in the same range, as the value found appropriate by Fujita et al [52,53] when modelling the precipitation sequence in ferritic stainless steels. They concluded that their experimental results for the M 6 C carbide could be reproduced by the use of an interfacial energy of 0.26 or 0.33 J/m 2 .…”
Section: Coarsening Of M 6 C Carbidesmentioning
confidence: 44%
“…The interfacial energies between group V transition metal carbides and Fe are well known and they are 0.26, 0.23 and 0.5 J/m 2 for Fe/NbC, Fe/NbN and Fe/VN system respectively. 3,5,6) The only reported interfacial energy for group IV transition metal carbide/Fe is 0.2 J/m 2 for Fe/TiC system. 7) As mentioned previously, experimentally obtained interfacial energies have uncertainties originated from too simple assumption adapted in theory as well as experiment errors.…”
Section: Interfacial Energy and Misfit Strain Energy Ofmentioning
confidence: 99%
“…The most general method used to obtain the interfacial energies is estimation of interfacial energy from experimental data of precipitate coarsening rate with the help of the Ostwald ripening law. [1][2][3][4][5][6][7] Recently, the discrete lattice plane/nearest neighbor broken bond (DLP/NNBB) approach was also employed by Yang and Enomoto 8) to calculate the energy of interfaces formed between ferrite (bcc Fe) and MCs or nitrides of Ti, V, Zr and Nb. The required bond energies in this approach were evaluated from the semi-empirical model of Boer et al 9) Because of a lack of reliability in the estimation of interfacial energy by empirical and semi-empirical methods, the ab initio method with a high physical accuracy has been recently used to calculate the interfacial energies.…”
Section: Introductionmentioning
confidence: 99%